A study of the effects of landbanking on the local economic development of the City of San Jose Del Monte, Bulacan - Sabitsana, Michelle P.M (School of Urban and Regional Planning, University of the Philippines Diliman, 2019)
This study ascertained the criteria, process, and issues of landbanking, identified the perceived effects of landbanking and the indicators of local economic development (LED), and suggested measures to harness or address the perceived effects to contribute to LED. For this study, landbanking was defined as the activity of acquiring and holding lands in advance or in anticipation of future uses. The LED indicators employed were economic activities, income/revenues, employment, and basic infrastructure and social services. The perceived effect of appreciation of land values had a direct link to the LED indicator of income or revenues due to the increase in real property tax base. Meanwhile, the perceived effect of project development had a direct link to the LED indicators of income or revenues and basic infrastructure and social services through the employment and revenues generated from the construction and operations of projects. However, due to limited data, the envisioned direct link of project development and enticement of other players to come in to the LED indicators of economic activities and employment could not be conclusively. Measures were also proposed to address the perceived effects to contribute to LED. For appreciation of land values, these measures included the enactment of special levy ordinance/s and prescription of period to develop reclassified properties. For land use changes, the measures included the strict, consistent, and uniform imposition of penalties for the unauthorized deviations from the ZO and the imposition of additional charges or certain concessions to justify the land use changes or deviations from the CLUP or the ZO. For enticement of other players or developments to come in, the recommendations included the institutionalization, funding, and promotion of CSJDM's Landbanking Program and enhancement of its project preparation capacities. For displacement, the recommendation focused on the continued implementation of CSJDM's Landbanking Program to secure sites for relocation and provide basic infrastructure and social services. Lastly, the study highlighted as a general strategy for LED by managing or harnessing the following perceived effects: (1) appreciation of land values- by beating inflation and rising land prices, thereby resulting in cost savings, increased real property taxes, and an inventory of available properties for future use; (2) land use changes- by having control over the lands acquired and leverage to demand concessions from potential investors or interested parties of said lands; 93) enticement of other players to come in-by allowing on the landbanked properties only those projects that are aligned with or guided by the CLUP and CSJDM's Vision; and (4) displacement - by providing properties for relocation that are replete with livelihood and social services.